2010
DOI: 10.1111/j.1365-2133.2010.09894.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of rosacea on quality of life: effects of demographic and clinical characteristics and various treatment modalities

Abstract: Rosacea affects patients' lives to a moderate extent, and this can be assessed by using DLQI. DLQI is also sensitive to quality of life changes brought about by treatment of rosacea. As a preliminary result we can say that topical metronidazole, oral tetracycline and oral isotretinoin seem to improve quality of life of patients by improving lesions of rosacea more efficiently than other therapeutic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
0
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 15 publications
6
101
0
13
Order By: Relevance
“…3 In contrast, a previous study found that, of the secondary features, only burning/stinging was significantly correlated with ETR while severity of this feature was associated with OC. 14 In that study, however, PPR was considered to be a subgroup of ETR, thereby reducing the sensitivity of detecting differences between ETR and PPR. The prevalence of ocular symptoms in 36% of this cohort is within the range of previous recent investigations from dermatology clinics.…”
Section: Discussionmentioning
confidence: 99%
“…3 In contrast, a previous study found that, of the secondary features, only burning/stinging was significantly correlated with ETR while severity of this feature was associated with OC. 14 In that study, however, PPR was considered to be a subgroup of ETR, thereby reducing the sensitivity of detecting differences between ETR and PPR. The prevalence of ocular symptoms in 36% of this cohort is within the range of previous recent investigations from dermatology clinics.…”
Section: Discussionmentioning
confidence: 99%
“…The DLQI questionnaire is a reliable and valid instrument that is quite sensitive to QoL changes brought about by various treatment options. 146,147 The rosacea-specific QoL and Skindex-29 measure which characteristics of rosacea affect the patient's life the most. Interestingly, flushing was found to be the most troubling symptom reported by patients affected by rosacea, stressing the importance of treating both the cosmetic and medical aspects of this condition.…”
Section: Patient-focused Perspectives: Quality Of Life and Patient Samentioning
confidence: 99%
“…It is important to remember that rosacea can lead to a lot of negative psychological effect in the patient and this in turn can lead to aggravation of the primary disease. 6 To break this vicious cycle, an effective treatment of the primary disease is of paramount importance. 6 In addition to the therapeutic options employed in the disease, avoidance of triggering factors, UV-protection and proper skin care are equally important in the management of rosacea.…”
Section: Introductionmentioning
confidence: 99%